2018
DOI: 10.13005/ojc/340211
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Lead (Ii) By Lumbang (Aleurites Moluccana) Activated Carbon Carboxymethylcellulose Composite Crosslinked with Epichlorohydrin

Abstract: Removal of Pb(II) using lumbang activated carbon carboxymethylcellulose composite crosslinked with epichlorohydrin was investigated. Batch adsorption studies were performed to evaluate the effects of pH, contact time, temperature, adsorbent dose, and metal concentration. To characterize the adsorbent, proximate analysis, bulk density, DSC, FT-IR, and SEM analysis were performed. Results of FT-IR revealed that crosslinking did not alter the structure of carboxymethylcellulose due to the presence of the -COO fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…The carbon from the candlenut shell produced in study generally has functional groups (types of bonds) found in carbon, including OH, C-H and C=O [15]. The functional groups identified on the carbonized shell of candlenut include O-H, C=C, C-H from the methyl and methylene groups, C-H from the aromatic structure.…”
Section: Resultsmentioning
confidence: 99%
“…The carbon from the candlenut shell produced in study generally has functional groups (types of bonds) found in carbon, including OH, C-H and C=O [15]. The functional groups identified on the carbonized shell of candlenut include O-H, C=C, C-H from the methyl and methylene groups, C-H from the aromatic structure.…”
Section: Resultsmentioning
confidence: 99%
“…Karbon dapat didefinisikan sebagai amorf yang memiliki porositas dan luas permukaan yang tinggi [5], karena struktur berpori ini, karbon aktif banyak digunakan dalam berbagai aplikasi, seperti adsorben zat warna [6], adsorben logam berat dan gas [7], katalis, elektroda (baterai dan superkapasitor) [8]. Karbon dapat disintesis dari biomassa yang tersusun dari lignoselulose.…”
Section: Pendahuluanunclassified
“…The meat from lumbang seeds was removed, and the shells were washed and sundried for a week. The lumbang shells were pyrolyzed following the method in previous studies 9,10,11,13 with slight modifications. Approximately 3 kg of lumbang shells were placed in a burrow with a diameter of 2 ft and a depth of 3 ft.…”
Section: Preparation Of Charcoalmentioning
confidence: 99%
“…Over time, researches have focused on the adsorption capabilities of different materials: biological materials, oxides, activated carbons, and polymer resins 6 . Among these, the use of activated carbon (AC) has become increasingly popular 7,8,9,10,11,12,13 , and it is highly favored due to its relative ease of regeneration, favorable adsorption kinetics, high adsorption capacity, and significant resistance to abrasion. There is a reliable number of sources for the production of activated carbon from agricultural wastes, such as coconut shells 12 and calamansi peels 14 , as alternative to coal and lignocellulosic materials 15 .…”
Section: Introductionmentioning
confidence: 99%